2017
DOI: 10.1016/j.neuroscience.2016.10.069
|View full text |Cite
|
Sign up to set email alerts
|

KLF7-transfected Schwann cell graft transplantation promotes sciatic nerve regeneration

Abstract: Abstract:Our former study demonstrated that Krüppel-like Factor 7 (KLF7) is a transcription factor that stimulates axonal regeneration after peripheral nerve injury. Currently, we used a gene therapy approach to overexpress KLF7 in Schwann Cells (SCs) and assessed whether KLF7-transfected SCs graft could promote sciatic nerve regeneration. SCs were transfected by AAV2-KLF7 in vitro. Mice was allografted by an acellular nerve (ANA) with either an injection of DMEM (ANA group), SCs (ANA+SCs group) or AAV2-KLF7-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 52 publications
(52 reference statements)
2
39
0
Order By: Relevance
“…Instead, many investigators have looked toward regulators of gene networks such as transcription factors of various regeneration-associated pathways. Here, we expanded upon previous reports of improved axonal regeneration and functional recovery attributed to the regulatory factor KLF7 established in the injured CST [ 10 , 12 , 36 ]. The goal of this study was to determine whether KLF7 treatment could be a novel strategy for DPSN axonal plasticity and functional repair after SCI.…”
Section: Discussionmentioning
confidence: 93%
“…Instead, many investigators have looked toward regulators of gene networks such as transcription factors of various regeneration-associated pathways. Here, we expanded upon previous reports of improved axonal regeneration and functional recovery attributed to the regulatory factor KLF7 established in the injured CST [ 10 , 12 , 36 ]. The goal of this study was to determine whether KLF7 treatment could be a novel strategy for DPSN axonal plasticity and functional repair after SCI.…”
Section: Discussionmentioning
confidence: 93%
“…SCs also migrate into the CNS and remyelinate axons SCI [19,20]. Since SCs secrete multiple growth factors, their inclusion show promise in therapeutic strategies for spinal cord repair [21][22][23][24]. In light of these benefits of SCs [25][26][27], we propose that SCs coupled with 3D channel scaffolds could aid axon regeneration in SCI.…”
Section: Introductionmentioning
confidence: 99%
“…It was further supported by SEM observation that oval BMSCs adhered and grew on the vessel wall of basilar membrane and presented uniform distribution. Although very few research argued against persistent survival of the seed cells after BMSCs laden‐ANX grafting in vivo (Hou et al, ), our previous studies found that labeled Schwann cells or BMSCs remained detectable and secreted neurotrophic factors in acellular nerve allografts or ANX at 4–8 weeks posttransplantation, irrespective of the species of the acellular nerve grafts (Jia et al, ; Wang et al, ). ANX thereby supplies the facilitating medium for the survival, adhesion, migration, and neurotrophic factors secretion of the seed cells.…”
Section: Discussionmentioning
confidence: 92%
“…Autologous nerve grafts are identified as the optimal nerve substitutes, nevertheless, the limited source of donor nerves and triggered denervation restrict the clinical application. Great progresses have been made in exploring natural and artificial nerve alternatives in decades (Du, Chen, Qing, Yang, & Jia, ; Li et al, ; Wang et al, ). Based on the chemical extraction, developed by Sondell, Lundborg, and Kanje (), the natural peripheral nerves were prepared into acellular nerve grafts with bioactivity for allogeneic and heterologous transplantation.…”
Section: Introductionmentioning
confidence: 99%